Analyzing Indonesian Cement Companies’ Efficiency Using the Stochastic Frontier Analysis Method Period 2014-2018 - Afina, Syadza; Hendrawan, Riko (Indonesian Journal of Multidisciplinary Science, 2023)
Cement industry is one of the important industries in supporting the country’s development. However, the level of cement utilization in Indonesia in 2014–2018 experienced a fluctuating growth. In 2014–2016, the decreased revenue growth had been followed by the decreased growth in net profit margin and return on assets, while the increased revenue growth in 2016–2018 was not followed by the increased growth in net profit margin and return on assets. Therefore, it is necessary to analyze the company’s efficiency to maintain its performance. The results of this study indicate that the variable of raw materials cost had a significant negative effect on efficiency, variable of labor cost, total assets, revenue, and interest rates had significant positive effects on efficiency, while return on equity and return on assets had no significant effect on efficiency. The most efficient cement company was Semen Indonesia, Ltd with a value of 0.93609 and the least efficiency one was Semen Baturaja, Ltd with a value of 0.09772.